Brief characterization of the behavior of the spiny rat Trinomys setosus (Rodentia: Echimyidae) in captivity - Bueno, Flávia Regina; Spinelli de Oliveira, Elisabeth; Klein, Wilfried (Therya Notes, 2021)
Hairy Atlantic spiny rats (Trinomys setosus, Echimyidae) are Neotropical caviomorph rodents belonging to an ecologically diverse group, that is relatively unknown from a behavioral point of view. Grooming is considered prevalent in rodents: wild and laboratory individuals employ grooming during 15–50 % of their waking time. We ask if grooming behavior in T. setosus is similarly low as in closely related species, and characterize the main behavioral categories seen in the species in detail. We quantified the occurrence of self-grooming (face washing, body washing, washing of the pelvic region, and scratching) during single 30-minute sessions of 16 adult individuals (four males and twelve females), in the context of activity, resting and maintenance categories (defecation and urination). The following behavioral categories were identified: 1) locomotor activity, 2) remaining motionless, 3) defecating, 4) face washing, 5) body washing, 6) washing the pelvic region, 7) scratching, 8) urinating, 9) shaking, 10) vocalizing. Grooming behavior followed the descriptions of stereotypical behavior observed in other rodent species and its occurrence represented 6.7 % (females) and 5.9 % (males) of the time studied. Grooming, seen across a great variety of animal taxa, involves numerous functions besides the primary role of body caring, which are of great importance for an animal’s well-being. Compared to commonly studied rodents, T. setosus spent relatively little time with grooming behavior, just as its sister species T. yonenagae.